O movimento homológico das formas na construção da modernidade - Rodrigues, Paulo Victor Ferreira (2018)
This research points to the multiple character of Baudelaire's eyes, multiple because he did not consolidate himself only in the lyrical genre, he focused on the tale, the novel, the music, the Plastic Arts, in short, on everything that is touching on art, regardless of the genus. Baudelaire perceived the condition sign wich walks in the interior of the artistic work and began, in the middle of the nineteenth century, an intense critical work. From this critical work translations of the work of Edgar Allan Poe came out and special attention was given to the tale The Man of the Crowd in the Essay The Painter of modern Life. In this essay Baudelaire traces the work of a painter, Monsieur G. (Mr.G), now known by critics, Constantin Guys. In addition to Constantin Guys, two other painters are placed on a par with Constantin Guys and are part of the second chapter because of the transgressive character of their works, transgressor in the sense of not following models so that the production of a work without a soul takes place. The works of art will be approached with the concept of artistic text wich Iuri Lotman (1978) conceptualizes in the book The structure of the artistic text and from the perspective of Julia Kristeva (2012) in the book Introdução à semanálise. Starting from this concept of text as a sign structure, semiotics will be used as a way of reading the object. One of the conclusions of the research was the multiplicity of paths left by these writers and painters, free ways for art to free itself from the bonds of a fixed way of composing. Art began to act on its own, to weave itself into the accompanying theory, and artists began to produce critical works by internalizing the need to be aware of their creative process.